BASIC Annual Review and Planning Meeting - Interview with Olusegun Ojo - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
BASIC Annual Review and Planning Meeting 2019 Held at IITA Ibadan, 11th - 13th March, 2019.